PENGGUNAAN CARBON FIBER REINFORCED PLATE SEBAGAI BAHAN KOMPOSIT EKSTERNAL PADA STRUKTUR BALOK BETON BERTULANG - Budiwirawan, Agung; Pengestuti, Endah Kanti (Universitas Negeri Semarang, 2010)
The flexural strengthening of reinforced concrete beam can be consideredwith applied externally bonded steel plate or carbon fiber composite. This externalplate is bonded to the tension face of the concrete beam. Experimental study onreinforced concrete strengthening with Carbon Fiber Reinforced Plate (CFRP) hasbeen conducted to estimate the effectiveness of using CFRP on the concretestructure as flexural strengthening material and external reinforcement. Twobeams were provided in this study to test the flexural strengthening effect ofexternally bonded CFRP composite. One of them was used for normal condition(BKT). The other specimen is the reinforced concrete beam with single steelreinforcement and laminated CFRP (BKTC). On the second beam, CFRPlaminated on the bottom of beam with epoxy. Dimension of the beams are150/250 mm with effective length 1900 mm. All beams were tested using twopointloading to get pure bending in the middle span. The result of theexperimental research showed that the ultimate load of the beam with externallybonded CFRP( BKTC) is 49% higher than BKT; stiffness of the strengthenedbeam BKTC is 68% higher than BKT; and cracking moment of the strengthenedbeam BKTC is 50% higher than BKT. However, the deformation and ductility ofthe strengthened beam BKTC is lower than BKT 77.6% and 73% respectively.The failure phenomenon of the concrete beam with laminated CFRP is priordebonding CFRP that makes maximum performance of the CFRP not be reached.Key words : CFRP, flexural strengthening, debonding failure